Functional diversity of the lepidopteran ATP-binding cassette transporters - Barve, Pranoti R.; Tellis, Meenakshi B.; Barvkar, Vitthal T.; Joshi, Rakesh S.; Giri, Ashok P.; Kotkar, Hemlata M. (Journal of Molecular Evolution, 2022)
The ATP-binding cassette (ABC) transporter gene family is ubiquitous in the living world. ABC proteins bind and hydrolyze ATP to transport a myriad of molecules across various lipid-containing membrane systems. They have been studied well in plants for transport of a variety of compounds and particularly, in vertebrates due to their direct involvement in resistance mechanisms against several toxic molecules/metabolites. ABC transporters in insects are found within large multigene families involved in the efflux of chemical insecticides and toxic/undesired metabolites originating from food and endogenous metabolism. This review deals with ABC transporter subfamilies of few agronomically important Lepidopteran pests. The transcriptional dynamics and regulation of ABC transporters during insect development emphasizes their functional diversity against insecticides, Cry toxins, and plant specialized metabolites. To generate insights about molecular function and physiological roles of ABCs, functional and structural characterization is necessary. Also, expansion and divergence of ABC transporter gene subfamilies in Lepidopteran insects needs more systematic investigation. We anticipate that newer methods of insect control in agriculture can benefit from an understanding of ABC transporter interactions with a vast range of natural specialized molecules and synthetic compounds.
Keywords: ABC transporters; Bt; insecticide resistance; Lepidoptera; Plant metabolites

High levels of sinigrin trigger synthesis of fatty acids in Plutella xylostella (L.) - Barve, Pranoti R.; Barvkar, Vitthal T.; Giri, Ashok P.; Kotkar, Hemlata M. (Comparative Biochemistry and Physiology D-Genomics & Proteomics, 2025)
Diamondback moth (Lepidoptera: Plutellidae; Plutella xylostella L.) is a specialist insect of the Brassicaceae family, damaging economically important crops, such as cabbage and cauliflower. Glucosinolates, also known as `mustard oil bombs' are present in all Brassicaceae members, of which sinigrin (allyl-glucosinolate or 2-propenylglucosinolate) is a major aliphatic compound. During herbivory, glucosinolates are converted to toxic isothiocyanates that deter insect pests. P. xylostella possesses glucosinolate sulfatases that desulfate them. Such a conversion renders them unfit for degradation to toxic products. Changes in the larval performance prompted us for RNA sequencing to understand probable adaptation mechanism under sinigrin stress. Differentially expressed genes were found to be related to larval cuticle proteins. Further, gene ontology and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses depict genes belonging to the categories, integral component of membrane, cellular processes and those involved in biosynthesis of fatty acids. Upregulation of cuticular genes viz. larval cuticle protein-17 (LCP-17), cuticular protein-19 (2CP-19) and ATP binding cassette transporter C7 (ABCC7), ABCC16 was validated by qRT-PCR. Liquid chromatography quadrupole time of flight mass spectrometry analysis of whole larvae feeding on sinigrin and their separated cuticle, depicted abundance of fatty acids. Changes in the topography of the larval cuticle were evident by scanning electron microscopy. Expression of PxABCH1 was corroborated to its role in the transport of cuticular lipids. Notably, molecular docking of PxABCH1 with cuticular fatty acids showed favorable binding interactions. To summarize, integrated transcriptomic and metabolomic analyses suggest that in response to a diet containing a high dose of sinigrin, P. xylostella re-programs metabolic pathways related to fatty acid biosynthesis that directly influence insect development.
Keywords: ABC transporter; Cuticle; Host metabolite; Metabolome; Plutella xylostella; Sinigrin; Transcriptome